2018
DOI: 10.1016/j.virol.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Expression and antiviral function of ARGONAUTE 2 in Nicotiana benthamiana plants infected with two isolates of tomato ringspot virus with varying degrees of virulence

Abstract: ARGONAUTEs (notably AGO1 and AGO2) are effectors of plant antiviral RNA silencing. AGO1 was shown to be required for the temperature-dependent symptom recovery of Nicotiana benthamiana plants infected with tomato ringspot virus (isolate ToRSV-Rasp1) at 27 °C. In this study, we show that symptom recovery from isolate ToRSV-GYV shares similar hallmarks of antiviral RNA silencing but occurs at a wider range of temperatures (21-27 °C). At 21 °C, an early spike in AGO2 mRNAs accumulation was observed in plants infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…As for the miR390a and miR393a, both of them were reported to bind to NbAGO2 protein competitively [41], therefore we speculated that this is the reason that they play similar role with miR403a in our experiments. Paudel et al reported that NbAGO2 expression was induced by tomato ringspot virus (ToRSV; Secoviridae ) isolates ToRSV-Rasp1 or ToRSV-GYV, and silencing of NbAGO2 elevated ToRSV accumulation [81]. This indicated that NbAGO2 was involved in plant responses toward different families of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…As for the miR390a and miR393a, both of them were reported to bind to NbAGO2 protein competitively [41], therefore we speculated that this is the reason that they play similar role with miR403a in our experiments. Paudel et al reported that NbAGO2 expression was induced by tomato ringspot virus (ToRSV; Secoviridae ) isolates ToRSV-Rasp1 or ToRSV-GYV, and silencing of NbAGO2 elevated ToRSV accumulation [81]. This indicated that NbAGO2 was involved in plant responses toward different families of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperatures allow more efficient viral RNA replication ( Zhang et al, 2012 ) and this is often associated with earlier symptom development ( Obrêpalska-Stêplowska et al, 2015 ). At lower temperatures, although the initial viral titer is lower, viruses accumulate to higher levels later on and consequently, more severe symptoms can develop at late stages of infection ( Szittya et al, 2003 ; Chellappan et al, 2005 ; Qu et al, 2005 ; Ghoshal and Sanfacon, 2014 ; Xu et al, 2016 ; Paudel et al, 2018 ). It is possible that the onset of antiviral RNA silencing, which is triggered when the viral RNA concentration reaches a critical level, occurs earlier at higher temperatures as a consequence of the enhanced virus replication.…”
Section: Prevalence Of Tolerance In Wild Ecosystems and Impact Of Envmentioning
confidence: 99%
“…For example, in the interaction between tomato ringspot virus and N. benthamiana , early onset of recovery is not accompanied with a significant reduction of viral RNA levels, although the concentration of viral proteins is reduced ( Jovel et al, 2007 ; Ghoshal and Sanfacon, 2014 ). Viruses present in recovered tissues maintain their infectivity and protect the plant against secondary infection in a sequence-specific manner ( Ratcliff et al, 1997 , 1999 ; Jovel et al, 2007 ; Santovito et al, 2014 ; Paudel et al, 2018 ). This has been attributed to the induction of antiviral RNA silencing during the symptomatic phase of infection ( Santovito et al, 2014 ).…”
Section: Symptom Recovery As An Inducible Form Of Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…AGO1 has the capability to target compact structure viral RNAs, while AGO7 favors less structured RNAs and both are involved in the silencing of Turnip crinkle virus (TCV) RNAs [120]. Ago1 , ago2 , and ago7 (knockdown) mutants show increased hyper-susceptibility to CMV, TCV, TMV, potato virus X (PVX) and ringspot virus [117,120,121,122,123,124]. Similarly, plants require AGO proteins (AGO4, AGO6, AGO9) for systemic silencing where AGO4 plays a crucial role in maintaining or activating the expression of stress-responsive genes via chromatin modification or preventing cryptic transcription [125,126].…”
Section: Plant Rna Silencing and Virusesmentioning
confidence: 99%